Problems of using "quest" technology in training in the process of professional development - Karshiyeva Dilnoza (International Journal on Orange Technologies, 2020)
In this article, we will discuss the problems in the design of qualification process lessons, the importance of pedagogical technologies in their elimination, the problems of using Quest technology in the organization of practical classes, the tasks and advantages.